Anti-multiple myeloma potential of resynthesized belinostat derivatives: an experimental study on cytotoxic activity, drug combination, and docking studies. Issue 34 (10th August 2022) - Nguyen, Hong Phuong; Tran, Quang De; Nguyen, Cuong Quoc; Hoa, Tran Phuong; Duy Binh, Tran; Nhu Thao, Huynh; Hue, Bui Thi Buu; Tuan, Nguyen Trong; Le Dang, Quang; Quoc Chau Thanh, Nguyen; Van Ky, Nguyen; Pham, Minh Quan; et al.
Abstract : Multiple myeloma is a deadly cancer that is a complex and multifactorial disease. Abstract : Multiple myeloma is a deadly cancer that is a complex and multifactorial disease. In the present study, 12 belinostat derivatives (four resynthesized and eight new), HDAC inhibitors, were resynthesized via either Knoevenagel condensation, or Wittig reaction, or Heck reaction. Then an evaluation of the antiproliferative activities against myeloma cells MOPC-315 was carried out. Amongst them, compound 7f was the most bioactive compound with an IC50 of 0.090 ± 0.016 μM, being 3.5-fold more potent than the reference belinostat (IC50 = 0.318 ± 0.049 μM). Furthermore, we also confirmed the inhibitory activity of 7f in a cellular model. Additionally, we found that the inhibitory activity of 7f against histone deacetylase 6 catalytic activity (HDAC6) is more potent than that of belinostat. Finally, we observed the strong synergistic interaction between the derivative 7f and the proteasome bortezomib inhibitor (CI = 0.26), while belinostat and bortezomib showed synergism with a CI value of 0.36. Taken together, the above results suggest that 7f is a promising HDAC inhibitor deserving further investigation.